Miara elastyczności organizacji - ewolucja modelu - Wawrzynek, Łukasz (Measuring organizational flexibility - an evolving model, 2005)
In a time of fast and unforeseeable changes in the market, organizations constantly have to adjust their ways of working to the changing environmental conditions. Flexibility thus becomes a most important category for management to consider. The level of flexibility defines whether an organization will be as effective tomorrow as is today. This article's goal is to propose a general method for measuring flexibility, being at the same time a continuation of the general model presented in 2001.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 167-173